Rancang Bangun Sistem Informasi Pemesanan Custom Furniture Berbasis Website - Utama, Damasius Wikaryana; Putra, I Gusti Lanang Agung Raditya; Satwika, I Putu (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Information is the king pin in business. Companies challenge their self to get an actual and factual information to be exist and win the tender. Companies are forced to use an up-to-date technology to produce the information needed. Especially in custom furniture company that has a long business process. It starts from measuring, modelling, budgeting, quotation, re-measuring, quality control, budget realization, until invoice printing. All of those processes must be organized in 1 management, so the custom furniture company can provide the actual and factual information for their customers. CV. Bali Interio is one of the company run in custom furniture business. This company has problems in their business process, it starts from the unorganized documents, slow processing documents que, messing measuring schedule, online buyer that doesn’t have an online media to buy, and the customers who want to monitor their order online. Based on the problems, it can be concluded that CV. Bali Interio needs a computerized system to solve the problems so it can give the best information needed for company or customer.